GLP-1 Receptor Activation Abrogates β-Cell Dysfunction by PKA Cα-Mediated Degradation of Thioredoxin Interacting Protein - Shijun He; Wenyu Wu; Yihong Wan; Kutty Selva Nandakumar; Xiuchao Cai; Xiaodong Tang; Shuwen Liu; Shuwen Liu; Xingang Yao; Xingang Yao (Frontiers Media S.A., 2019)
Glucagon-like peptide 1 receptor (GLP-1R) agonist (Exendin-4) is a well-known agent used to improve β-cell dysfunctions via protein kinase A (PKA), but the detailed downstream molecular mechanisms are still elusive. We have now found that PKA Cα mediated- TXNIP phosphorylation and degradation played a vital role in the β-cell protective role of exendin-4. After PKA activator (Exendin-4 or FSK) treatment, PKA Cα could directly interact with TXNIP by bimolecular fluorescence complementation and Co-IP assays in INS-1 cells. And PKA Cα overexpression decreased TXNIP level, whereas TXNIP level was largely increased in PKA Cα-KO β-cells by CRISPR-Cas9. Interestingly, TXNIP overexpression or PKA Cα-KO has impaired β-cell functions, including loss of insulin secretion and activation of inflammation. PKA Cα directly phosphorylated TXNIP at Ser307 and Ser308 positions, leading to its degradation via activation of cellular proteasome pathway. Consistent with this observation, TXNIP (S307/308A) mutant resisted the degradation effects of PKA Cα. However, exendin-4 neither affected TXNIP level in TXNIP (S307/308A) mutant overexpressed β-cells nor in PKA Cα-KO β-cells. Moreover, exendin-4 treatment reduced the inflammation gene expression in TXNIP overexpressed β-cells, but exendin-4 treatment has no effect on the inflammation gene expression in TXNIP (S307/308A) overexpressed β-cells. In conclusion, our study reveals the integral role of PKA Cα/TXNIP signaling in pancreatic β-cells and suggests that PKA Cα-mediated TXNIP degradation is vital in β-cell protective effects of exendin-4.